Impact of the COVID-19 Pandemic on The Choice of Economic Value of Students - Agnieszka GOZDEK; Aneta SOKOL (Communications of International Proceedings, 2020)
Colloquially, the term "value" is understood as something particularly valuable, meeting high requirements; it is something we want, desire and which is the goal of human aspiration. The values can be classified differently. One of these classifications takes into account economic values. In order to learn about the preferred values and their hierarchical arrangement, the authors of the articles decided to study the impact of the coronavirus pandemic on the volatility of economic values among students. This social group, shaping its economic values at this stage of life, will in the future influence the processes of economic socialization of the next generations. Therefore, the article verifies the research hypothesis: The Covid pandemic determines a change in the approach to economic values among the young generation. The aim of the research will be to examine a group of young people through the use of focus group interviews in terms of changes or lack thereof resulting from the pandemic in their economic values. And the conclusion for the research was the answer to the following research question: In the opinion of the respondents, did economic values change under the influence of the conditions arising in the covid pandemic among young people? The verification of the research assumptions allowed to indicate that the change in economic values among the studied group under the influence of the coronavirus pandemic is rather invisible according to the surveyed students.
Keywords: value; economic value; covid; pandemic.